Diagnosis of Pulmonary Tuberculosis in Children - Gunadi Santosa (Paediatrica Indonesiana, 1975)
1. A definite diagnosis of tuberculosis can only be established on the basis of the finding of the tubercle bacilli.2. The isolation of the mycobacterium tuberculosis from a child is subject to difficulties:a. the necessity of gastric lavage for 3 consecutive days, which is difficult to perform ambulatory.b. the necessity of the proper facilities of a microbiologic laboratory.c. the outcome is often not sufficiently high.3. It is concluded that at the moment making of the bacteriological diagnosis of child tuberculosis is not practical, so that we are forced to depend on the clinical diagnosis.4. The tuberculin test is very important in establishing the diagnosis. It is recommended to perform this test routinely on every child once a year and also that every medical doctor as well as specialist performs this test to detect a case of TBC at the earliest possible moment.